2013
DOI: 10.1002/jgrd.50437
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric electric parameters and micrometeorological processes during the solar eclipse on 15 January 2010

Abstract: [1] Indian scientists got the unique opportunity to study the near-Earth environment during a long annular solar eclipse at the end of the last long deep solar minimum, on 15 January 2010. Continuous high time resolution records of the atmospheric electric parameters and meteorological parameters were made at Tirunelveli (8.07 N, 77.08 E, 35 m Above Mean Sea Level (AMSL) and Braemore Hill (8.41 N, 76.59 E, 460 m AMSL) stations where the eclipse was during 11:07:57-15:06:52 IST with maximum obscuration (~90%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous reports from other sites have identified that a significant (order 60%) reduction in PG is generally observed during an eclipse [23,[31][32][33][34][35][36]. These measurements were taken at low geomagnetic latitudes (less than 40 • ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports from other sites have identified that a significant (order 60%) reduction in PG is generally observed during an eclipse [23,[31][32][33][34][35][36]. These measurements were taken at low geomagnetic latitudes (less than 40 • ).…”
Section: Discussionmentioning
confidence: 98%
“…Relatively few studies of this nature have been undertaken based on a dense network of meteorological stations, due to the relative rarity of solar eclipses taking place across suitably instrumented regions during modern times. However, previous studies, usually based on one to a few recording sites rather than dense station networks, report surface air temperature dips during solar eclipses of approximately 3 • C (Paraguay [2]), 1.7-2.1 • C (Germany [3]), 0.3-1.5 • C (Svalbard [4]), 1.2-4 • C (India [5][6][7]), up to 2.5 • C (Korea [8]), 0.7-3.9 • C (Greece [9,10]), 3.0 • C (Antarctica [11]) and 3 • C (Florida, USA [12]). Several workers also present evidence of an eclipse-related decrease in near-surface wind speed that can be attributed to more stable conditions in a cooler boundary layer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example during the 11 August 1999 total solar eclipse transient a temperature decreases of up to 3 °C and a mean regional wind speed decrease of 0.7 m s −1 during the maximum eclipse hour with a mean anticlockwise wind direction change of 17° were observed (Gray and Harrison 2012). Also the electric parameters of the atmosphere change: the ambient electric field dropped by up to 65% during the eclipse, and potential gradient showed epochs of enhancements during and after the eclipse until after Sunset (Anil Kumar et al 2013). The authors conclude that during the course of an eclipse, radiative cooling enables the formation and development of water droplets resulting in scavenging or coalescence of free ions/free space charges in the atmosphere causing the decreases in electric currents and field strengths with the reduction in galactic cosmic rays flux as possible additional effect.…”
Section: Environmental Studiesmentioning
confidence: 97%